The Review of compression stocking in sports market - Inmaculada Aparicio-Aparicio; Jose Luis Sanchez-Jimenez; Ignacio Catala-Vilaplana; Pedro Perez-Soriano; Clara Carrion-Gonzalez (European Journal of Human Movement)
Sport companies offer a diversity in compression garments according to its purpose. Athletes use these garments to recover/improve their performance. However, literature shows controversy at their results and companies offer a wide range of products. The aim of this study was to analyse the current sport compression stockings market in compression, size, and properties. Seventeen commercial brands offering compression sport stockings were examined and the principal claims were to improve performance (n = 43), recovery (n = 10) and combination of performance and recovery (n = 13). Sizes, compression values, and type of compression (gradual or uniform) varies among brands, and between different models at the same brand. The most reported properties in the sport compression market are protection, followed by comfort, blood flow and breathability. While the least claimed properties in the sport compression market are delayed onset muscle soreness mitigation, thermoregulation (freshness-preserving and warmth-retaining insulation), and risk of injury reduction. The lack of information observed in the compression stockings market and the heterogeneity in test procedures, types, and levels of compression in the literature makes the comparison between products difficult. Greater rigor when analysing garments and their effects is required at the claims of the companies in their products.